Kwaterunek wojskowy w domach prywatnych Księstwa Warszawskiego Regulacje prawne - Filipiak, Zbigniew (Studia Iuridica Toruniensia, 2011)
<!–[if gte mso 9]> <![endif]–> The theme of this publication is the obligation of quartering soldiers in private homes during the existence of the Warsaw Principality. This particular duty, to which the young citizens of this state were obliged, was a form of restricting the right to own a private property. The article presents the regulation of military lodgings of the years 1807 to 1812. It is worth noticing the attempt to introduce the lawful procedures and to provide a partial (since limited to lodgings of off icers) cash compensation scheme for homeowners that fall under the above mentioned obligation. Unfortunately, the disastrous condition of the fi nances of the Principality did not allow, in most cases, for the remuneration of legally paid quarters. <!–[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>